Assessment of surface and ground water quality around Korba Coalfield, India: an integrated approach of water quality index, multivariate statistics analysis and GIS technique - Dheeraj V.P.; Singh C.S.; Sonkar A.K.; Kishore N. (My University, 2025)
Groundwater as well as surface water are considered to be an important source of freshwater. An Opencast mining operations and thermal power stations in the Korba Coalfield region may have a negative impact on both ground and surface water thus, it reduces the water quality. Hence, an attempt is being made for social benefits to people living in this region by analyzing the water quality. A total of 52 ground and surface water samples are collected in May 2022, and twelve physicochemical parameters were calculated in reference to it. The concentrations of EC, TDS, NO3−, SO42−, Ca2+, Mg2+, Na+, and K+ exceeded at a few sites as compared with WHO standards. As a consequence, it has been observed that the order of cation abundance as Ca2+ > Na+ > Mg2+ > K+ whereas anionic abundance HCO3− > Cl− > SO42− > NO3− > F−. Water facies studies indicate that CaMg-HCO3 and CaMg-Cl-SO4 represented by majority of ground and surface water samples. Gibbs diagram in respect to cation and anion reveals that rock dominance & evaporation dominance are the two most important factors influencing the quality of water. Based on the correlation matrix, it is noted that there are significant positive correlations between EC-TDS, EC-Ca2+, EC-Mg2+, EC-HCO3−, TDS-Ca2+, TDS-Mg2+, TDS-HCO3−, Cl-K+, Ca2+-Mg2+, and Mg2+-HCO3−, and strong negative correlations between F−-NO3−. The majority of water samples 69.2% has excellent water quality, followed by 26.9% with good water quality and only 3.8% with poor water quality based on WQI value. A general trend of increasing physicochemical parameters are highlighted by the spatial distribution map. As per HCA analysis, the number of sampling sites are highest for Cluster 1 (63.46%), medium for Cluster 2 (32.69%), and lowest for Cluster 3 (3.84%), as per WQI. Hence, The ground and surface water in the vicinity of the Korba Coalfield can be utilized for drinking and other purposes after little treatment. © 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.